Connectedness to Nature and to Humanity: their association and personality correlates - Lee, Kibeom; Ashton, Michael C.; Choi, Julie; Zachariassen, Kayla (Frontiers in Psychology, 2015)
People differ in the extent to which they identify with humans beyond their ingroup and with non-human living things. We refer to the former as the Connectedness to Humanity (CH) and to the latter as the Connectedness to Nature (CN). In a sample of 324 undergraduate students, CH and CN were operationalized using the Identification with All Humanity Scale (McFarland et al., 2012) and the CN Scale (Mayer and Frantz, 2004), respectively. These variables correlated moderately with each other (r = 0.44) and shared Openness to Experience and Honesty–Humility as their primary personality correlates. CN was found to play an important role in mediating the relationships between the two personality variables and some specific pro-environmental/pro-animal attitudes and ecological behaviors.